Evolution of Thoracic Surgery at BP Koirala Memorial Cancer Hospital, Nepal: An 18 – Year Journey of Innovation and Growth. - Thakur, Binay; Devkota, Mukti; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee; Kharel, Asish; Adhikari, Mahesh Mani; Sapkota, Sandeep (Nepalese Journal of Cancer, 2025)
Background: Thoracic malignancies constitute 15% of Nepal’s cancer burden, with lung cancer being the leading malignancy. This study aims at evolution of thoracic oncosurgery services at BP Koirala Memorial Cancer Hospital (BPKMCH) - Nepal’s premier tertiary cancer hospital during a period of 18 years (2007- 2025) to highlight procedural innovations, survival trends and resource-adapted strategies.Methods: a retrospective analysis of 8683 surgical procedures stratified into: Foundation (2007-2010; open surgery), Expansion (2011-2015; Minimally Invasive transition), and Modernization (2016-2025, June; precision surgery). Data sources included hospital records, surgical database, and institutional publications.Results: major surgeries increased 9-fold (106 in 2007 to 951 in 2024). Video-assisted thoracic surgery (VATS) biopsies achieved 98% diagnostic yield. Minimally invasive esophagectomy (MIS esophagectomy) rose from 0% to 80% (p